Enforcing the GNU general public licence: copyright or contract? - Dysart, T; Thomas Dysart (2014)
The GNU General Public Licence (GPL) is one of the most widely used licences in the field of Free and Open Source Software (FOSS). Principally a legal document drafted to facilitate the development, use and transfer of software, the licence also embodies a strong ideological character that seeks to challenge the paradigmatic representation of software as property. At its core, the GPL places great emphasis on the licensee’s freedom to view, use, modify and distribute a covered work. However, for all its claims to openness and freedom, the GPL functions by way of restrictions. These restrictions are primarily designed to prohibit privatisation of the work by downstream licensees, but they also restrict other forms of conduct deemed contrary to the established practices of FOSS development. This paper asks a seemingly simple legal question, yet it is one that is deeply entangled in the ideological and strategic complexities of a field that has received little in the way of judicial clarification. The question is whether the GPL’s restrictive provisions are contractual in nature or merely property-based restrictions that act unilaterally to define the scope of the granted rights. Focusing almost exclusively on Anglo-American jurisprudence, this paper will consider a variety of licensing issues relating to formalities, the nature and scope of rights, and remedies in order to determine on which side of the property/contract divide the GPL's restrictive provisions reside, or perhaps should reside.